EVALUATING THE EFFECTIVENESS OF ONLINE BANKING APPS - Barredo, Leo Andrei; Berdugo2, KC B; Dublon, Mary Rica; Vasquez, Michael B (President University, 2024)
Online banking applications have transformed financial management by allowing users to access banking services anytime and anywhere. The effectiveness of the online banking apps have been established through varied sources but there is a paucity in the literatures locally as well as utilization of the evaluative perceptions of Purisimian students. This study investigates the effectiveness of the online banking apps among the college students of Colegio de la Purisima Concepcion applying a mixed-method methodology using explanatory sequential design. Sequentially, the quantitative data were collected from the randomly selected 332 respondents through a validated and pilot-tested researcher-made questionnaire. Subsequently, the qualitative data were gathered from the six participants through an in-depth interview. The study investigated the online banking apps' effectiveness across context, input, process, and product dimensions considering the demographic variables like age, sex, and department affiliation. Quantitative analysis utilized frequency counts, percentages, t-test, and analysis of variance, while the qualitative analysis followed Colaizzi's method. Results showed that online banking apps are perceived as highly effective overall, but their effectiveness varies notably based on the sociodemographic profile such as age and department affiliation. While users generally perceive these apps positively, differences in perception exist regarding their context, input, process, and product among distinct demographic groups. This research enriches the literature by highlighting the need to consider user demographics in designing online banking apps to enhance user experience and satisfaction.